Consumer Acceptability of Empanada stuffed with Rabbit meat (Lapanada) Using Baking and Frying Method of Cooking - Jocelyn Espiritu; Eleonora Uy; Michelle Gatdula (Camarines Sur Polytechnic Colleges, 2022)
This study aimed to develop a healthier version of the empanada by using rabbit meat (lapan) and to determine its consumer acceptability through empanada stuffed with rabbit meat (lapanada). An experimental research design was used to evaluate the product using a 9-category Hedonic scale method to be selected by thirty (30) semi-trained panelists from Bulacan Agricultural State College. Deep fat frying and baking methods were used in the development of the product, with three (3) different percentages of lapan meat being used as the main ingredient of "lapanada". The study revealed that in terms of crust, the baking method was slightly more acceptable than deep-fat frying. In terms of meat filling, 50% of lapan meat was the most acceptable. Analysis of variance on attributes of fillings in terms of appearance has no significant difference with the methods used. However, in terms of aroma, savory, and mustiness, the fillings were significant and highly significant to the baked method of cooking "lapanada." Also, in terms of texture, the results showed that there was no significant difference with its methods used. The result of the study was a product pioneer or bearer of BASC when it comes to utilizing rabbit meat (lapan) as the main ingredient of the food product. Standard procedures for Lapanada processing were subjected to intellectual property protection to ensure secrecy of the process and trade product. It is recommended to conduct further studies for the shelf-life test and nutrient analysis of "lapanada" to establish the credibility of the product in terms of microbiological characteristics and nutritive value. Market research must be conducted to establish empirical data as a benchmark for future improvements.